Durable superamphiphobic coatings from one-step electrostatic dusting. Issue 37 (21st August 2019) - Zhang, Youfa; Xiao, Zhen; Liu, Chengzhi; Yu, Xinquan
Abstract : Superamphiphobic coatings are fabricated via electrostatic dusting using modified silica particles and polymethyl methacrylate resin particles on conductive substrates (metal and conductive glass). Abstract : Superamphiphobic coatings are fabricated via electrostatic dusting using modified silica particles and polymethyl methacrylate resin particles on conductive substrates (metal and conductive glass). The obtained translucent superamphiphobic coatings show excellent durability and chemical robustness even after exposure to strong acids and bases. Importantly, the coatings maintain hydrophobicity even after 100 cycles of abrasion testing and 1000 cycles of finger wiping. In addition, the fabricated coatings are superoleophobic after finger wiping, tape peeling and oil immersion. This facile strategy may provide researchers in related fields with new avenues for improving powder coatings in practical applications.